2015
DOI: 10.1007/s10518-015-9742-1
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterization of the out-of-plane performance of regular stone masonry walls, including test setups and axial load influence

Abstract: Stone masonry is one of the oldest and most worldwide used building techniques. Nevertheless, the structural response of masonry structures is complex and the effective knowledge about their mechanical behaviour is still limited. This fact is particularly notorious when dealing with the description of their out-of-plane behaviour under horizontal loadings, as is the case of the earthquake action. In this context, this paper describes an experimental program, conducted in laboratory environment, aiming at chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 25 publications
1
22
0
Order By: Relevance
“…The mechanical parameters of the materials have been selected with the aim of covering a broad and meaningful set of realistic situations rather than to analyze the response of 2 masonry bonds specifically related to the church façades selected for the present research. Considering that the external layers of the 2 masonry typologies can be described as “squared limestone blocks” for bond‐texture (1) and “regular clay bricks” for bond‐texture (2), the mechanical properties have been assigned in agreement with the recent literature, as well as with the Italian building code for existing masonry building (eg, Ministero delle Infrastrutture e dei Trasporti, table C8A.2.1 and C8A.2.2). The internal layer has been considered as the weakest part, usually made by rubble stones and broken bricks.…”
Section: Discrete Models Of the Masonry Façadesmentioning
confidence: 88%
See 1 more Smart Citation
“…The mechanical parameters of the materials have been selected with the aim of covering a broad and meaningful set of realistic situations rather than to analyze the response of 2 masonry bonds specifically related to the church façades selected for the present research. Considering that the external layers of the 2 masonry typologies can be described as “squared limestone blocks” for bond‐texture (1) and “regular clay bricks” for bond‐texture (2), the mechanical properties have been assigned in agreement with the recent literature, as well as with the Italian building code for existing masonry building (eg, Ministero delle Infrastrutture e dei Trasporti, table C8A.2.1 and C8A.2.2). The internal layer has been considered as the weakest part, usually made by rubble stones and broken bricks.…”
Section: Discrete Models Of the Masonry Façadesmentioning
confidence: 88%
“…[25][26][27][28] For the purposes of the present study, the numerical modelling should be efficient, to perform full nonlinear dynamic analyses with an acceptable computational effort, but not simplistic, since the damage response of the building materials, in the context of the composite nature of the 3-leaf masonry walls, should be properly included. [29][30][31][32] Special attention should be devoted to the definition of a reasonable nonlinear material response compatible with the experimental evidence as well as with analytical and microstructure numerical modelling, 16,33,34 by accounting for the static vertical compression, the 3-leaf bond effects, the internal friction, and the progression of damage with hysteretic dissipation.…”
Section: Out-of-plane Damage Mechanismsmentioning
confidence: 99%
“…The application of a uniform out-of-plane loading pretends (as was observed) to globally mobilize the out-of-plane response of the IM wall. In the literature similar out-of-plane load distribution adopted by other authors can be found (Griffith et al, 2007, Ferreira et al, 2015. This reaction structure is composed by five vertical and four horizontal alignments of rigidly connected steel bars, in front of which a vertical wooden platform is placed to resist the airbag pressure and transfer it to the steel reacting grid elements.…”
Section: Out-of-plane Test Setup Descriptionmentioning
confidence: 99%
“…A wide range of sophisticated mechanical models have been developed to predict the nonlinear behavior of masonry material both in tension (low tensile capacity with consequent cracking phenomena) and compression, including individual failure and damage mechanisms (Ferreira et al 2015a). Unfortunately, some of these models are rather difficult to apply to the 3D analysis of complex structural systems, not only because of the large number of parameters involved in the definition and updating of the mechanical model but also because of the number of DoF required to mesh the structure .…”
Section: Materials Properties and Model Parametersmentioning
confidence: 99%